Proper Application of the 3-Way Fumigant System for the Post-Methyl-Bromide Era - Andrew W. MacRae (EDIS)
HS1174, a 2-page fact sheet by Andrew W. MacRae, describes the 3-Way system — using a combination of three fumigants to achieve control of nematodes, diseases, and weeds — as a methyl-bromide alternative for the control of soilborne pests, and discusses considerations for growers in selecting fumigant systems. Published by the UF Department of Horticultural Sciences, May 2010.